2022
DOI: 10.1021/acs.est.2c02976
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Biochar, Bacteria, and Plants for Sustainable Remediation of Soils Contaminated with Organic Pollutants

Abstract: The contamination of soil with organic pollutants has been accelerated by agricultural and industrial development and poses a major threat to global ecosystems and human health. Various chemical and physical techniques have been developed to remediate soils contaminated with organic pollutants, but challenges related to cost, efficacy, and toxic byproducts often limit their sustainability. Fortunately, phytoremediation, achieved through the use of plants and associated microbiomes, has shown great promise for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(50 citation statements)
references
References 241 publications
0
46
0
4
Order By: Relevance
“…They have an important role in rhizospheric bacterial chemotaxis and solubilization of phosphorus [ 41 ]. In addition, the PGPB has been documented to decrease pollutant levels and be useful for revitalizing organic pollutant-contaminated soils [ 42 ]. It has been reported that PGPB can induce the conversion of petroleum hydrocarbons, polychlorinated biphenyls, and pesticides into nontoxic products or minerals [ 42 ].…”
Section: Plant Beneficial Microorganismsmentioning
confidence: 99%
“…They have an important role in rhizospheric bacterial chemotaxis and solubilization of phosphorus [ 41 ]. In addition, the PGPB has been documented to decrease pollutant levels and be useful for revitalizing organic pollutant-contaminated soils [ 42 ]. It has been reported that PGPB can induce the conversion of petroleum hydrocarbons, polychlorinated biphenyls, and pesticides into nontoxic products or minerals [ 42 ].…”
Section: Plant Beneficial Microorganismsmentioning
confidence: 99%
“…Organic additions, such as poultry manure, enhance soil characteristics by increasing organic matter content, which has a stimulating influence on structure and aggregate stability. When compared to other organic sources, poultry manure is an extraordinary source of organic fertiliser because it includes a high percentage of nitrogen, phosphorous, potassium, and other critical elements that are readily available for plant absorption (Xiang et al, 2022). It enhances soil physical properties and conditions, as well as nutrient absorption and crop yield (Arora et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The combined effect of the two pesticides reduced their bioavailability. Yu Xiangyang et al investigated the influence of pesticides on the killing effectiveness of target plants and pests by applying biochar made from wheat and rice straw to the soil and discovered that the herbicides Diuron (50) and clomazone (51) were successful in destroying weeds, but the efficacy has been reduced. In other words, pesticide absorption by target plants and pests is relatively low, reducing pesticidal efficacy.…”
Section: The Effects Of Biochar Application On Pesticide Bioavailabil...mentioning
confidence: 99%